2019
DOI: 10.1007/s11269-019-02313-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wind Flow and Solar Radiation on Functionality of Water Evaporation Suppression Monolayers

Abstract: The average evaporation in Iran is 3 times higher than the world average. Applying chemical monolayers on water surfaces is one of the promising methods for suppressing the evaporation. Literature studies have shown that the mixture of cetyl and stearyl (ratio of 1 to 9) is the state-of-the-art monolayer to minimize the evaporation. Adding calcium hydroxide increases the spreading rate and self-healing of the monolayer. Despite long study and investigation on monolayers, there are inconsistencies in explaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…So, a considerable drop was observed in both pans on the SD because of the rst windy day. Since the oating pans experience waves inside, more cracks or holes will appear in the lm, therefore using a component to ll in cracks and help respreading becomes important (Mozafari et al, 2019). In order to overcome this problem St and Ce can be mixed in which the shorter one (Ce) helps spreading rate and ll in the cracks and the longer one (St) acts more as an evaporation retardant (Prime et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…So, a considerable drop was observed in both pans on the SD because of the rst windy day. Since the oating pans experience waves inside, more cracks or holes will appear in the lm, therefore using a component to ll in cracks and help respreading becomes important (Mozafari et al, 2019). In order to overcome this problem St and Ce can be mixed in which the shorter one (Ce) helps spreading rate and ll in the cracks and the longer one (St) acts more as an evaporation retardant (Prime et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It also disappeared on the SD in the oating pan due to emerging into wavy water in windy condition (Brzozowska et al, 2012) and didn't achieve to save appropriate TW. In order to improve stability and increase spreading rate of the layer, the CH were added to F4 to make F6 (Mozafari et al, 2019) which indicated more than 50% R in the FD on both land and oating pans. The CH dissolves in the water and make positive charged Calcium ions that makes the F4 spread all over the surface because of positive repel force and can resist against wind up to 4.5 m/s (Waheeb Youssef and Khodzinskaya, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations